2018
DOI: 10.1016/j.apgeochem.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the solid solution - Aqueous solution system (Ba,Sr,Ra)SO4 + H2O: I. The effect of strontium content on radium uptake by barite

Abstract: Thermodynamic properties of mixing in the ternary (Ba,Sr,Ra)SO 4 solid solution are determined using first principles based total energy calculations and Monte Carlo simulations. Two levels of theory, which correspond to the regular mixing and the generalized Ising model, are considered. The results show that the regular mixing parameters increase along the row of Ba-Ra, Ba-Sr and Sr-Ra binary systems proportionally to the squared difference of molar volumes of the end-members. The magnitudes of pairwise inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 35 publications
2
53
0
Order By: Relevance
“…In an earlier study [8] we noticed that in large super-cell calculations a full geometry optimisation led to slight deviations from the orthorhombic symmetry, but this was not explored further. Similar calculations carried out here reproduced the result and the structure shown in Vinograd et al [8], where the SO 4 -groups are slightly rotated in comparison to the orthorhombic structure ( Fig. 5).…”
Section: Dft Calculationsmentioning
confidence: 99%
“…In an earlier study [8] we noticed that in large super-cell calculations a full geometry optimisation led to slight deviations from the orthorhombic symmetry, but this was not explored further. Similar calculations carried out here reproduced the result and the structure shown in Vinograd et al [8], where the SO 4 -groups are slightly rotated in comparison to the orthorhombic structure ( Fig. 5).…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Studies on the thermodynamics of (Ba x , Sr 1−x )SO 4 solid solutions are still under active development (37), and one of the uncertainties is the interaction parameter of Ba-Sr ions in (Ba x , Sr 1−x )SO 4 solid solutions, which determines the ideality (SI Appendix, section 1.3) and the free energy of mixing (SI Appendix, section 1.4) of the solid solution (35)(36)(37)(38)(39). Using the interaction parameters developed by different models (35,36), the calculated compositions (i.e., x) varied to some extent but were all in general consistent with the measured compositions of (Ba x , Sr 1−x )SO 4 .…”
Section: Sr Enrichment In Heterogeneous (Ba X Sr 1−x )So 4 Precipitmentioning
confidence: 99%
“…Inspection of Table and Figure shows that the higher the Sr‐content in the host solid, the lower the equilibrium concentration of Pb in the aqueous solution. Vinograd et al () have also observed that trace amounts of SrSO 4 in the barite solid solution improves Ra‐uptake. In practice, reaching equilibrium requires the parent solid to be completely dissolved and recrystallized, which maybe kinetically hindered.…”
Section: Application To Ternary Systemsmentioning
confidence: 92%